VD_FINDINFO HC / 2014 / 686 vom 31. Juli 2014 - VD Tribunal cantonal (2014)
MESURE PROVISIONNELLE, OBLIGATION D'ENTRETIEN, PREUVE FACILITÉE, VISITE | 176 al. 1 ch. 1 CC, 176 al. 3 CC, 276 CPC (CH), 308 al. 1 let. b CPC (CH), 312 al. 1 CPC (CH)